(untitled) - HADLEY, G. (USA, 1961)
1.Linear models / 2.Linear algebra / 3.Leontiefs interindustry model of an economy / 4.Linear programing / 5.Graphical solution of a linear programming problem in two variables / 6.Regression analysis / 7.Linear circuit theory / 8.Other linear models / 9.The road ahead / 10.Vectors / 11.Physical motivation for the vector concept / 12.Operations with vectors / 13.The scalar product / 14.Generalization to higher dimensions / 15.Generalized vector operations / 16.Euclidean Space and the scalar product / 17.Linear dependence / 18.The concept of a basis / 19.Changing a single vector in a basis / 20.Number of vectors in a basis for E a la n / 21.Orthogonal bases / 22.Generalized coordinate systems / 23.Vector spaces and subspaces / 24.Matrices and determinants / 25.Matrices / 26.Matrix operations / 27.Matrix multiplication / 28.Vector and matrices / 29.Identity , scalar , diagonal and null matrices / 30.The transpose / 31.Symmetric and sskew - symmetric matrices / 32.Partitioning of matrices / 33.Basic notion of a determinant / 34.General definition of adeterminant / 35.Some properties of determinants / 36.Expansion by cofactos / 37.Additional properties of determinats / 38.Laplace expansion / 39.Multiplication of determinats / 40.Determiant of the porduct of rectangular matrices / 41.The matrix inverse / 42.Properties of the inverse / 43.Computation of the inverse by partitioning / 44.Produt form of the inverse / 45.Matrix series and the Leontief inverse / 46.Linear tranformations , Rank and elementary transformations / 47.Definition of linear transformacions / 48.Properties of linear tranformations / 49.Rank / 50.Rank and determinats / 51.Elementary tranformations / 52.Echalon matrices and rank / 53.Simultaneous Linear equations / 54.Gaussian elimination / 55.Cramers rule / 56.Further properties / 57.Homogeneous linear equations / 58.Geometric interpretation / 59.Basic solutions / 60.Convex sets and n - Dimensional geometry / 61.Sets / 62.Point sets / 63.Lines and hyperplanes / 64.Convex sets / 65.The convex hull / 66.Theorems on separating hyperpalnes / 67.A basic result in a linear programming / 68.Convex hull of extreme points / 69.Introduction to convex cones / 70.Convex polyhedral cones / 71.Linear transformations of regions
Incluye indice analitico pag.287
Keywords: ALGEBRA LINEAL